DAMPAK WORK LIFE BALANCE TERHADAP PRODUKTIVITAS SDM DI ERA HYBRID WORKING - Zulkarnaini, Zulkarnaini; Haholongan, Rutinaias (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to analyze the effect of work-life balance (WLB) on human resource (HR) productivity in the hybrid working era. The research method used was a quantitative approach with a survey technique, involving employee respondents from companies implementing a hybrid work system. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The results showed that work-life balance had a positive and significant effect on HR productivity. Of the three work-life balance indicators, psychological engagement had the most dominant influence, followed by time balance and role satisfaction. These findings confirm that mental stability and work-life balance are key to increasing employee effectiveness, efficiency, and target achievement. The study concludes that organizations that support work flexibility through hybrid working policies, mental wellness programs, and fair reward systems can improve employee well-being and organizational productivity. This research provides practical implications for HR management in integrating work-life balance as a strategy for sustaining productivity in the modern work era.